Whole Body Vibration Attenuates Brain Damage and Neuroinflammation Following Experimental Traumatic Brain Injury - Chen, Tao; Liu, Wen-Bo; Ren, Xu; Li, Yun-Fei; Li, Wei; Hang, Chun-Hua; Wang, Yu-Hai (Frontiers in Cell and Developmental Biology, 2022)
Traumatic brain injury (TBI) is still a major public health problem worldwide, and the research of neuroprotective drugs has encountered great difficulties. Whole body vibration (WBV) is a safe and powerful rehabilitative intervention in various clinical settings, but its effect on neurological diseases is not well documented. In this study, we investigated the effects of WBV pretreatment on brain damage following experimental TBI mimicked by controlled cortical impact (CCI) in mice. C57BL/6J male mice were expose to WBV at 30 Hz twice per day for 20 days and injured by CCI. WBV had no effect on animal body weight, but significantly reduced the TBI-induced brain edema in the cortex. The results of immunostaining showed that the activation of microglia and astrocytes induced by TBI in brain sections was attenuated by WBV. In consistent, WBV markedly inhibited the expression of pro-inflammatory cytokines, while increased the levels of anti-inflammatory cytokine interleukin 10 (IL-10). In addition, WBV pretreatment alleviated neuronal apoptosis in the cortex and suppressed the cleavage of the apoptotic executive molecule caspase-1. The neurological dysfunction following TBI was determined by open field test and Morris Water Maze (MWM) assay. The results showed that motor activity, learning and memory ability were preserved by WBV compared to TBI-injured mice. In summary, our present data identified WBV as a clinically potent strategy with which to attenuate TBI-related brain damage through regulating neuroinflammation.